ORGANISASI PEREMPUAN DAN PEMBANGUNAN KESEJAHTERAAN - M Zainal Anwar (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
This paper would like to see how the women organizations have tried to build prosperity for women, especially women who live in the village. Interestingly , the women organization activists seek a way out of poverty by using their own ideas, perspectives and mindset, not guided by a uniform national policy. This means the ideas are built based on local emancipation where women live day-to- day. In the author’s view, one way for women to achieve prosperity is to give them a chance to work. For women , the purpose of giving the opportunity to work not only to increase revenue but also to take care of a variety of social vulnerability , especially poverty and domestic violence. Women’s access to work also means the opportunity to be involved in the socio - political relations more broadly. This means that women can contribute to the development of their neighbourhood because they no longer dwell in the domestic sphere, but have enough time to interact in the public sphere , especially through the involvement in an organization. By doing so, the involvement of women in the organization has a broad meaning, not just a mere social benefit. There is a transformation of social capital, in the form of involvement in the organization, into economic capital in the form of an opportunity to engage in economic activity. However, the effort to transform social capital into economic capital is not easy . There are still unfavourable views arguing that women capability is not commensurate with men which eventually limit women to access a livelihood. Therefore, it is necessary to find a perspective that places men and women in equal and fair positions, especially in acquiring , utilizing and developing assets and accesses to economic resources , social and political . It is time for the state to formulate public policies that put women as the main actors and not merely as objects or complementary policies. In sum , this paper believes that by involving in an organization, women will have a greater opportunity to be involved in economic activities, which in turn can lead women to welfare gates .